Cross-sectoral relations in the delivery of public services - Savignon, Andrea Bonomi; Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio (Emerald Publishing Limited, 2018)
This volume presents and discusses evidence on collaboration between government, businesses and non-profits, focusing on an inter-organizational perspective of managing at the boundaries between sectors
Keywords: Nonprofit-Organisation; Öffentliche Dienstleistung; Politische Steuerung; Öffentlicher Sektor; Privatwirtschaft; Europa; Human services; Social policy; Aufsatzsammlung